TRACK FORMATION BY α-PARTICLES IN THE SOLID STATE TRACK DETECTORS - D’yachkov, V.V.; Yushkov, A.V. (Recent Contributions to Physics, 2021)
The nuclear and atomic mechanisms interaction of the incident α-particles with substance of the solid state track detectors that consist of polyethylene terephthalate and its analogs realized. The geometry of primary abeyance track was constructed as basic for detecting nuclear reactions products for range to 150 MeV.